EFFECTS OF ROBUSTA COFFEE BEAN EXTRACT (Coffea robusta) ON THE VIABILITY OF NEUTROPHILS EXPOSED BY Porphyromonas gingivalis - Tantin Ermawati (UPT Penerbitan Universitas Jember)
The new paradigm evolving today in thetreatment of periodontal infection is the use a hostmodulator therapy i.e. therapy that aims to improvethe host immune response to bacterial infection.Good immune response is necessary in increasingthe phagocytic function that in this case is played byneutrophil cells, monocytes and macrophages, whichserved as the first line of defense against bacterialinfections. One of the bacteria causing periodontalinfection is P. gingivalis. It has the biggest role incausing periodontal disease, where in the proteolyticenzyme such as gingipain contributes to thebacterial pathogenicity.1, 2 During the initial invasionP. gingivalis will colonize the gingival sulcus andinvade into the gingival tissues and will induce aninflammatory response and continue to alveolarbone resorption.3The immune response that acts first againstinvading bacteria is neutrophils. The presence ofbacterial adhesion to neutrophils allows neutrophilssecrete microbicidal substance by destroying thebacterial membrane and fagocyting bacteria. Aneutrophil can phagocyte bacteria before becominginactive or cell lysis. Phagocytosis that occurs canaffect the lysis of neutrophils. This can emerge veryfatal impacts because if the neutrophils undergo lysisthen chemical components and enzymes may breakinto the tissue leading to degradation of variousorganic molecules of its adjacent tissue.4 NowdaysIndonesia has developed a lot of research onmedicinal plants, such as Robusta coffee beans.Robusta coffee beans naturally have substances suchas caffeine, phenolic compounds, trigonellin andchlorogenic acid which have antibacterial activity.Besides as antibacterial chlorogenic it also hasantioxidant properties.5 Based on the abovebackground, the researchers want to developRobusta coffee beans as host modulator therapy tomaintain the viability of neutrophils by observingneutrophil cell viability against P. gingivalis appliedby Robusta coffee bean extract which will be usefulfor preventing periodontal tissue infections of theoral cavity.